A Rare Case of Deradelphus Cephalo‐Thoracoomphalopagus in Lamb. (3rd December 2012) - Lanteri, G.; Macrì, F.; Marino, F.; Caracappa, S.; Mazzullo, G.
Summary Male cross‐breed lamb conjoined twins were sent for examination. The twins came from a farm located in the outskirts of Palermo. The twins were spontaneously delivered and found dead by the farmer. X‐ray examination and necropsy were performed. The deformity was identified as deradelphus cephalo‐thoracoomphalopagus. This condition has never been reported in veterinary literature. Our case reports of male conjoined twins characterized by two separated hearts with their own pericardial sacs and two separated livers. These findings represent a rare condition in conjoined twinning.